Pengaruh Pemahaman Akuntansi, Penggunaan SIA, dan SPI Terhadap Kualitas Laporan Keuangan BUMDES - Ni Wayan Mamik Suwandewi; Sang Ayu Putu Arie Indraswarawati; Ni Putu Yeni Yuliantari (Hita Akuntansi dan Keuangan, 2026)
This study aims to determine the effect of accounting understanding, the use of accountinginformation systems, and internal control systems on the quality of BUMDes financial reportsin Tampaksiring District. The research method used is a quantitative approach with multiplelinear regression analysis. The population in this study were all BUMDes employees totaling45 people and the sample in this study were parties or users of BUMDes financial reports inTampaksiring District totaling 40 people. The sample collection method used purposivesampling. The results of this study indicate that accounting understanding has a positive andsignificant effect on the quality of financial reports. The use of accounting information systemshas a positive and significant effect on the quality of financial reports. The internal controlsystem has a positive and significant effect on the quality of financial reports. The implicationof this study is that BUMDes administrators need to improve their understanding of accounting,accounting information systems, and internal control systems in order to produce better qualityfinancial reports.